Lord Cooke and Patents: The Scope of "Invention" - Frankel, Susy (Victoria University of Wellington Law Review, 2008)
What inventions are patentable is the core issue in patent law. Lord Cooke, when he was a Court of Appeal judge, ruled that the definition of invention, under the Patents Act 1953, included the part of the Statute of Monopolies of 1623 known as the proviso. Amongst other things the proviso excludes matters that raise prices of commodities at home or are generally inconvenient from being inventions for the purposes of the Act. Cooke J held that the presence of the proviso meant that when patents are applied for inventions that raise matters of economic concern the courts should resist breaking new ground and Parliament should deal with the matter. In reaching that interpretation of the definition of invention Cooke J said that because of the diversity of international views on the patentability of methods of medical treatment, the Court could not shut its eyes to the fact that the application before it might result in raising prices of commodities at home or be generally inconvenient. At the core of Cooke J’s reasoning was the particular economic questions that arise for a country the size of New Zealand. This article discusses the treatment of Cooke J’s approach in the courts and in the patent registration system. The article also discusses the role of public opinion concerning economic and social policy issues arising in the patent system. The article concludes that Cooke J’s interpretation should continue to guide New Zealand’s approach to what is an invention, and thus what is patentable subject matter.